Project finance: uma modalidade de financiamento aplicada a energia eólica do Ceará - Martins, Allisson David de Oliveira (2010)
This work emphasizes the importance of the eolic energy and demonstrates the eolic potential technically profitable in the Ceará State. It specifically investigates a financial modality named Project Finance, through its definitions, risks, advantages and disadvantages. It also demonstrates the role played by the Project Finance as an alternative of long term credit, which is able to make feasible new projects related to the diversify of the Brazilian energetic matrix. The Project Finance structure is studied for eolic projects in Ceará, with the participation of Banco do Nordeste do Brasil S/A. In the analysis process of these financial planes, there are considered: the basic entrepreneurship characteristics, in their technical, economic and financial determinants; capital structures; entrepreneurship guarantees; risk factors and mitigators instruments. The work concludes that the Project Finance is very important for the entire Region, because presents itself as an important tool to the concretization of large projects, as the private enterprises play the role of big investors in the energy sector.